Coronavirus disease 2019 in an elderly patient who became severely ill despite antibody cocktail therapy but improved with lung-protective management: A case report - Mitsutome, Eriko; Une, Kazunobu; Nakanuno, Ryuichi (International Journal of Medicine, 2022)
Casilivimab/imdevimab, called antibody cocktail therapy, is a treatment for mildly and moderately ill COVID-19 patients. In our care facility, we encountered an elderly patient treated with an antibody cocktail after being diagnosed with a moderate disease at the initial presentation that became severe. An 80-year-old man with a history of diabetes, hypertension, and cerebral infarction presented with a 5-day history of fever and was diagnosed with coronavirus disease 2019. He was diagnosed with moderate disease and immediately ad-ministered the antibody cocktail therapy. However, his respiratory status deteriorated rapidly, and mechanical ventilation was initiated. We performed lung-protective ventilation, centered on low tidal volume and prone position therapy, with good outcomes. Throughout the pandemic, his case, as well as others, highlighted that immediate intervention for mild and moderate cases and intensive treatment, such as lung-protective ventilation and prone position, for severe cases improved patient outcomes.Â Â Â